Assessing rainwater adequacy for crops cultivation under varying rainfall probabilities in the Blue Nile region, Sudan - Ahmed, Shaker Babiker Ahmed; Yousif, Lotfie A. Yousif; Hassan Elhaj Alsayim; Saeed, Amir B Saeed (University of Khartoum Engineering Journal, 2025)
Abstract: Amount of rainfall and period between rainfall events play a fundamental role in watering rainfed crops, hence improving productivity. Rainfed agriculture in Blue Nile region is one of the important areas in the Sudan. This study was conducted to evaluate the adequacy of seasonal rainfall compared to crop water requirements (ETc) for major rainfed crops grown in the Blue Nile region under five climatic conditions: wet, semi-wet, normal, semi-dry, and dry seasons. Daily climate data were obtained from Sudan Metrological Authority (SMA) records during the period from 1971 to 2021. Start, end and length of the growing season were determined for the five season types. Rainwater before, during and after the growing season were calculated. Seven summer crops were studied namely; sorghum, millet, sesame, sunflower, groundnuts, soya bean and cotton. Crops life cycle, length of growth stages and crop coefficients were used to calculate ETc. The results indicated that while early-season rainfall often meets crop demands, mid and late-season deficits are common, particularly in semi-dry and dry seasons. Though total rainfall was adequate, its uneven distribution underscores the necessity for using suitable crop management and soil moisture conservation practices. The study concluded that all studied crops are viable under current rainfall regimes in Blue Nile region, however, suitable crop management and soil moisture conservation practices has to be considered during mid and late season.